Web Based Kampar Regency Tourism Information System - Prihatna, Jaka; Yusnira; Marwa, Safni (Journal of Engineering Science and Technology Management, 2024)
Tourism is one of the most popular destinations for tourists today, one of the tourist objects and destinations is in Kampar Regency. Kampar Regency has great potential in the tourism sector. Both in the form of historical heritage such as the Muara Takus Temple, the Koto Panjang Hydroelectric Reservoir, the Jami Mosque in Kampar District, and many other tourist attractions that are quite interesting to visit. The aim of the research is to design and create a tourism information system for Kampar Regency to make it easier for tourists to access information on tourist attractions in Kampar Regency. This research method uses a qualitative descriptive approach. Data is collected from interviews, field notes, documents and so on, then described and analyzed using triangulation so that it can provide clarity on reality. The research results show that with this system, it is easier for tourists to find information on tourist attractions, especially in Kampar Regency. The system provides photos of tourist information and its location, so that tourists get an idea of the profile of the tourist spot they are going to. It is hoped that this web-based tourism information system will make it easier for the public to obtain information about the locations of tourist attractions in Kampar Regency. The programming language used is the PHP Framework Laravel and MySQL as the database storage medium.